Effect of weeds as coverts in soil fertility and pecanal walnut yield - Martínez Díaz, Gerardo (Revista Mexicana de Ciencias Agrícolas, 2019)
The objective of this work was to evaluate the effect of the weed as a long-term covert in the soil fertility and performance of the pecanal walnut Carya illinoinensis (Wangenh.) K. Koch. The work was developed in the 32-year-old Western cv, under drip irrigation, in the coast of Hermosillo, Sonora. The treatments consisted of weed-based vegetation covering and the clean control, which were distributed in a design of paired plots with four replications, with an experimental unit of three trees per row. In content of organic matter, pH and most of the nutrients in the soil, it was higher in the treatment with coverts than in the control (p< 0.05) ten years after the beginning of the work, while the salinity of the soil was not modified. The average performance during the evaluation period was similar (p< 0.05) in both treatments. The greatest changes in the content of organic matter and concentration of nutrients occurred in the first 30 cm of depth. There were changes in fertility and salinity in the soil profile, but they were independent of the cover. The results show that in adult orchards of pecan tree, weeds can be used as coverts to improve the quality of the soil without affecting the performance of the pecanal walnut.
Keywords: alternation, interference, nutrients, salinity, weed.